KINERJA KEUANGAN MATAHARI DEPARTMENT STORE Tbk - Danna Solihin (RJABM (Research Journal of Accounting and Business Management), 2019)
The increasing advanced technology developments have changed the pattern of people’s lives, including in terms of fulfilling their daily needs. The use of internet media and various online application services has provided a lot of convenience to carry out transactions in the sale and purchase of goods and services. PT Matahari Department Store, which is one of the largest retail companies in Indonesia, has experienced the impact of this change in recent years.This study aims to analyze the financial performance of PT Matahari Department Store. The data used is secondary data obtained through the financial statements of PT Matahari Department Store which are published on the Indonesia Stock Exchange for the period of 2016-2018.Based on the analysis of the decline in financial performance for the period 2016 – 2018 which is viewed from the liquidity ratio through the current ratio, solvency ratio through total debt to total asset ratio and profitability ratio through return on assets.